TRAINING IN MANUFACTURING ANIMAL FEED JUICE FOR BREEDERS IN BANTURUNG DISTRICT, BUKIT BATU DISTRICT PALANGKA RAYA CITY - Seth Miko; Yesninopy; Saifulloh Darlan; Wahidin; Kusnida Indrajaya; Hendrowanto Nibel; Susan Daniel; Endah Yusma Pratiwi; Ade Yusuf Ferudyn; Mardiana; Muhamad Affandi (BALANGA: Jurnal Pendidikan Teknologi dan Kejuruan, 2024)
The purpose of writing this article is to provide knowledge about alternative feed to breeders in Banturung sub-district. 2) provide technical training in making animal feed juice. The research method used is the demonstration method. Demonstration is a training process carried out through demonstrations and practice given by the trainer to members including listening to and seeing the technical skills taught by the trainer. (Kartika, et al. 2023). Direct or Face-to-Face Training This method involves a training session where the instructor or facilitator provides explanations directly to participants. This training can be carried out in the form of lectures, presentations, or practical demonstrations at relevant locations, such as feed factories or farms. This approach allows participants to interact directly with the instructor and gain an in-depth understanding of the process of making animal feed juice. Based on the results of community service in Banturung sub-district, training in making animal feed juice is very beneficial for farmers considering that animal feed juice is an innovation that has been carried out. Animal feed juice is the result of processing various natural feed ingredients such as fruit into a liquid form of fermentation that is easily digested by livestock. This processing process aims to increase the availability of quality and nutritious feed for livestock, by utilizing local feed ingredients or agricultural waste available around the farm. The advantages of animal feed juice include increasing the nutritional value of feed. The process of processing animal feed juice can increase the nutritional content of natural feed ingredients, thereby providing a more balanced and nutritious intake for livestock. This can improve overall livestock health and productivity.